Nonlinear behavior and damage model for fractured rock under cyclic loading based on energy dissipation principle - Li, Tiantao; Pei, Xiangjun; Wang, Dongpo; Huang, Runqiu; Tang, Hao (Engineering fracture mechanics, 2019)
•The nonlinear behavior of fractured rock subject to cyclic loading has been presented.•A damage model for fractured rock is established.•This model takes into account the initial damage of rock and introduces the concept of equivalent modulus. In practical engineering, it is a common phenomenon of rocks subjected to cyclic loading. Such as mining engineering, subgrade engineering and earthquake engineering. In order to reveal the deformation properties of rock under cyclic loading and to establish the damage model, two groups of cyclic loading tests are carried out. Natural rocks show a remarkable nonlinear deformation property under the cyclic loading. The test results also reveal the evolutions of the elastic modulus and the residual strain of fractured rock. Energy dissipation is the essential characteristic of rock deformation and failure. Therefore, a damage model for fractured rock is established from the viewpoint of energy dissipation. This model takes into account the initial damage of fractured rocks and introduces the concept of equivalent modulus, which make the model more practical and easier to apply.